Asymmetric conjugate additions to pyridine and quinoline - Wettlaufer, David G., author; Meyers, A. I., advisor (Colorado State University. Libraries, 1984)
Extensive studies have investigated the stereochemical and mechanistic aspects of NADH (nicotinamide adenine dinucleotide)mimics. With potential use in mind, chiral 4-methyl and 4-phenyl-1,4- d ihyd ropy rid ines were synthesized by alkylation of 3- oxazolinylpyridine. (This oxazoline and the oxazolinylquinoline below were derived from (1S,2S)-1-phenyl-2-amino-3-methoxypropanol). Addition of excess methyllithium gave the dihydropyridines, isolated as the methyl urethanes, in 85-90% de and 79-81% yield. This high stereoselectivity was found to be independent of temperature and concentration. The oxazoline was readily removed to the aldehyde in 60% yield fil quaternization with methyl fluorosulfonate followed by reduction and hydrolysis. Phenyllithium addition gave the addition products in 84% de and 94% yield. Chiral 4-methyl-1,4-dihydropyridines were also synthesized by alkylation of 3-imino pyridines with excess methyl cuprates. These imines were prepared from 3-pyridinecarboxaldehyde condensed with phenylalaninol, phenylalaninol methyl ether, (S)-ethylvalinate, and (S)-t-butylvalinate. The highest stereoselectivity was realized upon alkylation of the t-butylvalinate imine to give the dihydropyridines as the methyl urethanes in 56% de. Mild acid hydrolysis yielded N-carbomethoxy- 3-foDT\Yl-4-methyl-l,4~ihydropyridines in 82% yield.
Covers not scanned.
Keywords: Aromatic compounds -- Synthesis